Illocutionary Speech Acts of Ustaz Salim A. Fillah Lecture Video in The Culture Edition - Nuri Puji Hastuti; Muhammad Rohmadi (UIN Salatiga, 2023)
Culture as the basis of speech acts can encourage the speaker and the listener to realize their goals in communication activities. The reasons are that culture can make listeners want to hear more about the speaker's information, can be media for listeners to illustrate the implicature, and can make them respond quickly. However, no specific research describes the culture, implicature, and response in the illocutionary speech acts to realize the effectiveness of communication. Based on this problem, it is important to do further research. The first purpose is to describe the illocutionary speech acts in Ustaz Salim A. Fillah's lecture video, especially in the Culture edition. The second purpose is to describe how culture, as part of illocutionary speech acts to realize the effectiveness of communication. The research used a descriptive qualitative method. The analysis data technique refers to the four simultaneous processes by Miles, Huberman, and Saldana, which consist of data collection, data reduction, data display, and conclusion. Speech acts are found to consist of assertive (identification, prediction, or description), directive (invocation, suggestion, or instruction), commissive (something is a must be conducted), expressive (expression of feeling), and declarative (acknowledgment of status or condition). All of those speech acts can make listeners want to hear more information, to be media to illustrate the implicature, and make them easier to remember the utterance of Ustaz Salim A. Fillah speech acts.